1999
DOI: 10.1046/j.1365-2141.1999.01752.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased serum levels of vascular endothelial growth factor predict risk of progression in early B‐cell chronic lymphocytic leukaemia

Abstract: The present study is the first to evaluate serum levels of vascular endothelial growth factor (VEGF) in B‐cell chronic lymphocytic leukaemia (CLL). All 68 B‐cell CLL patients and 31 control subjects analysed had detectable serum levels of VEGF, with no statistically significant difference between two proups. An aberrant increase of circulating levels of VEGF was found in only 17.6% of cases. B‐cell CLL patients whose serum VEGF levels were higher than the median (i.e. 194.8 pg/ml) or 75th percentile (i.e. 288.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
77
2
2

Year Published

2000
2000
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(84 citation statements)
references
References 31 publications
3
77
2
2
Order By: Relevance
“…VEGF and b-FGF concentrations were determinated by using a quantitative ELISA technique (Human VEGF and human b-FGF, Quantikine TM and Quantikine 1 ; R&D Systems, Minneapolis, MN, USA) as previously reported (Molica et al, 1999). Concentrations were reported as pg ml 71 .…”
Section: Cll Patientsmentioning
confidence: 99%
See 2 more Smart Citations
“…VEGF and b-FGF concentrations were determinated by using a quantitative ELISA technique (Human VEGF and human b-FGF, Quantikine TM and Quantikine 1 ; R&D Systems, Minneapolis, MN, USA) as previously reported (Molica et al, 1999). Concentrations were reported as pg ml 71 .…”
Section: Cll Patientsmentioning
confidence: 99%
“…Other assays b-2 m and LDH serum levels were determinated as previously described (Molica et al, 1999).…”
Section: Cll Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher levels of VEGF in serum or plasma have been evaluated as a predictor of outcome in patients with several malignant diseases (Dirix et al, 1996;Crew et al, 1997;Salven et al, 1997;Kraft et al, 1999;Molica et al, 1999). Recently, it has also been suggested that the patients with metastatic prostate cancer have higher plasma VEGF levels than those with localized disease or healthy controls (Duque et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the level of circulating VEGFin peripheral blood has been shown to be associated with angiogenesis, growth, dissemination, metastasis, and poor outcome irLsoHd or hematological malignancies (3)(4)(5)(6). Accordingly, for clinicians, knowledge of measurement of the VEGFlevel in peripheral blood should be emphasized.…”
mentioning
confidence: 99%